Political Science - Mahmood Monshipouri (International Institute of Islamic Thought, 1997)
Adopting an issue-oriented approach toward understanding Islamic and Western political thought, Professor Abdul Rashid Moten places these two tradition's within historical and contemporary contexts. Moten's book thereby provides a comparative analysis of key issues, including Islamic research methodology, Islamic law, Islamic political and social order, strategies and tactics of various Islamic movements, and the link between Islam and politics. In chapter 1, Moten examines the secular domination of Muslim thought and culture, arguing that secularism was imported into the Muslim world through the efforts of a Westernized elite. He adds that no such secular state had ever existed in the Muslim world. This owes much to the fact that there was (is) no common ground between Islam and secularism (p. 7). With secularism came nationalism, liberal political institutions, and the pursuit of a capitalist economic system. Nationalism, Moten notes, wedged its way into the Muslim world, dividing it into new nation-states and client states (p. 12). Since independence, secularism has failed to meet the socioeconomic and political needs of Muslim societies. The rising tide of Islamic revivalism against secular regimes in Algeria and Turkey demonstrates disenchantment with the shattered secularist dreams in the Muslim world (p. 16). Chapter 2 attempts to scrutinize the inherent link between Islam and politics. The pillars of Islam, Moten writes, go beyond moral and spiritual upliftment; they entail both practical and symbolic significance in all aspects of life. In Islam, ethics sets the tone for politics, and the rules of political behavior originate from ethical norms. Political life cannot be separated from the broader framework of the religious and spiritual life (p. 21 ). Islamic rulers have hardly, if ever, emphasized the separation of religion and politics. Since the nineteenth century, Islamic modernists and revivalists have debated the nature of this separation. The reemergence of Islam in Muslim politics and societies in the last quarter of the twentieth century has pointed to a distinct Islamic order and the reawakening of Muslim identity. Moten cites, among others, Iran and Pakistan as examples of such a renaissance (p. 30). However, he fails to examine the divisive effects of lslamization programs in Pakistan (under Zia al-Haqq) and other countries such as Sudan. The comparison between Western and Islamic methods of political inquiry is the subject of close scrutiny in chapter 3. Moten maintains that the Islamic conception of polity is based on profound religious-cultural grounds and that religion and polity form an organic unity (p. 37). Likewise, ethics and politics are ...